Moisture Loss from Cheese During Baking: Influence of Cheese Type, Cheese Mass, and Temperature - Justyna Tarapata; Ewa Szymańska; Liesbeth van der Meulen; Joost Miltenburg; Thom Huppertz (Foods)
This study examined how temperature, cheese mass and moisture content impact moisture loss rate in various cheeses during baking. Understanding these factors is essential for determining the browning properties of cheese during baking. Eight cheese types, differing in moisture content, were baked at 100–200 °C in a halogen moisture analyzer, and moisture loss over time was recorded. A mixed-effects model analysis showed that temperature had the most significant impact on moisture loss rate (F = 2008.54; p < 0.00001), followed by cheese mass (F = 1973.28; p < 0.00001) and time (F = 278.49; p < 0.00001). Higher temperatures and larger cheese mass accelerated moisture evaporation rate. The moisture content of cheese explained 21.8% of model variation, suggesting that other factors, such as cheese structure, also play a significant role. The cheese baking process involving moisture removal followed by distinct drying stages. Initially, the drying rate increased as the cheese reached the wet bulb temperature; this was followed by a steady rate, and finally, a reduction in dehydration rate as the moisture decreased, limiting further evaporation. Browning, assessed through changes in lightness (L*), was more noticeable at higher temperatures, particularly in Mozzarella and processed Cheddar, after approx. 30% moisture loss in all cheeses.